The 5-Ws of immunotherapy in head and neck cancer. (September 2020) - Botticelli, Andrea; Mezi, Silvia; Pomati, Giulia; Cerbelli, Bruna; Di Rocco, Christiana; Amirhassankhani, Sasan; Sirgiovanni, Grazia; Occhipinti, Mario; Napoli, Valerio; Emiliani, Alessandra; Mazzuca, Federica; Tomao, Silverio; et al.
Graphical abstract: Abstract: The immune checkpoint inhibitors, a class of drugs able to block immune suppressive pathways in order to prime an anticancer immunity, revolutionized standard of care in platinum-refractory recurrent and/or metastatic head and neck carcinoma (R/M HNSCC). The PD-1/ PD-L1 axis is involved in the genesis, maintenance and progression of HNSCC and represents the target of checkpoint inhibitors. HNSCC is an immunosuppressive disease with a high inflammatory component in tumor microenvironment. Recent clinical trials showed that only a small subset of patients really benefits from immunotherapy. This review aims to highlight the five W-points of immunotherapy: why immunotherapy is promising in HNSCC, what is currently available in daily clinical practice, when immunotherapy can be integrated into the therapeutic strategy, where it can be useful according to predictive response biomarker, who, among patients, could get the best benefit from immunotherapy and how improve the achieved results.